Emerging Roles of Redox-Mediated Angiogenesis and Oxidative Stress in Dermatoses. (16th April 2019) - Xian, Dehai; Song, Jing; Yang, Lingyu; Xiong, Xia; Lai, Rui; Zhong, Jianqiao
Abstract : Angiogenesis is the process of new vessel formation, which sprouts from preexisting vessels. This process is highly complex and primarily involves several key steps, including stimulation of endothelial cells by growth factors, degradation of the extracellular matrix by proteolytic enzymes, migration and proliferation of endothelial cells, and capillary tube formation. Currently, it is considered that multiple cytokines play a vital role in this process, which consist of proangiogenic factors (e.g., vascular endothelial growth factor, fibroblast growth factors, and angiopoietins) and antiangiogenic factors (e.g., endostatin, thrombospondin, and angiostatin). Angiogenesis is essential for most physiological events, such as body growth and development, tissue repair, and wound healing. However, uncontrolled neovascularization may contribute to angiogenic disorders. In physiological conditions, the above promoters and inhibitors function in a coordinated way to induce and sustain angiogenesis within a limited period of time. Conversely, the imbalance between proangiogenic and antiangiogenic factors could cause pathological angiogenesis and trigger several diseases. With insights into the molecular mechanisms of angiogenesis, increasing reports have shown that a close relationship exists between angiogenesis and oxidative stress (OS) in both physiological and pathological conditions. OS, an imbalance between prooxidant and antioxidant systems, is a cause and consequence of many vascular complains and serves as one of the biomarkers for these diseases. Furthermore, emerging evidence supports that OS and angiogenesis play vital roles in many dermatoses, such as psoriasis, atopic dermatitis, and skin tumor. This review summarizes recent findings on the role of OS as a trigger of angiogenesis in skin disorders, highlights newly identified mechanisms, and introduces the antiangiogenic and antioxidant therapeutic strategies.